Elementi e materiali di diritto doganale - Moriconi, Luca (Milano University Press, 2023)
The book was created as a study and support tool for the teaching and practical-laboratory activities of the three-year degree course in International Sciences and European Institutions (EIS) at the Department of International, Legal and Historical-Political Studies of the University of Milan and aims to offer a systematic overview of customs regulations, as a specific technical aspect within the broader context of the discipline of international trade. One of the main objectives is to make students, and all those who approach customs matters, perceive the absolute concreteness of the same, dwelling on the illustration of the main institutes, procedures and technical elements that form the basis of customs assessment. As a complement, the regulatory framework governing trade restrictions is then presented, with particular reference to the control of exports of dual goods, highlighting the delicate aspect of the related penalties and the strategic importance of a conscious and adequate approach to the discipline on the subject. From the overall picture, it clearly emerges how compliance in customs matters today represents a decisive factor in the qualification of trustworthy economic subjects, which is becoming increasingly important in the scenario of international trade relations. A number of in-depth materials are recalled and integrated in the text, to allow a more detailed analysis of specific aspects relating to the topics covered.